Impact of the strategy of administrative communication on the level of ￼Functional performance of workers in the junior sector in the Algerian ￼ - لوط محمد الصديق; بن مصباح كمال (Journal of Sport Science Technology and Physical Activities, 2019)
The objective of the research is to learn about the reality of the communication strategy of the Algerian professional football teams and how effective they are in raising the level of performance of the administrative and technical human resources working in the sector of the young people, and to answer the question, the researcher relied on the descriptive curriculum type survey, and The study sample included 36 Administrators , 24 coaches, 6 technical Managers in six professional teams in the east, and used the questionnaire as a means of data collection. The study found that the strategy of communication at the level of the Algerian teams in relation to the youth sector suffers from several shortcomings, including: the concealment of information and the poor communication competence of Administrators and coaches , as well as the higher management of the clubs do not listen in the form necessary for the concerns of the administrators and technicians, and therefore the study recommended the need to take care of the coming up and down and strengthen the communication culture of the administrators and coaches by subjecting them to the formation of communication and listening to the concerns and complaints of administrators and coaches working in the sector of the beginners and try to solve them because Responsible for the success or failure of the Young talent Formation project in the team